2009
DOI: 10.1124/dmd.109.028704
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Excretion of Anacetrapib, a Novel Inhibitor of the Cholesteryl Ester Transfer Protein, in Humans

Abstract: ABSTRACT:Anacetrapib is a novel cholesteryl ester transfer protein inhibitor being developed for the treatment of primary hypercholesterolemia and mixed dyslipidemia. The absorption, distribution, metabolism, and excretion of anacetrapib were investigated in an openlabel study in which six healthy male subjects received a single oral dose of 150 mg and 165 Ci of [ 14 C]anacetrapib. Plasma, urine, and fecal samples were collected at predetermined times for up to 14 days postdose and were analyzed for total radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 8 publications
2
31
0
Order By: Relevance
“…As discussed in the companion article on the metabolism of anacetrapib in humans (Kumar et al, 2010), the only metabolites detected in biological matrices (plasma and feces) from healthy human volunteers given a single 150-mg oral dose of [ 14 C]anacetrapib were M1, M2, and M3. All of these metabolites were present at much lower levels than those of the parent in human plasma (Ͻ14% of total plasma, radioactivity).…”
Section: Downloaded Frommentioning
confidence: 99%
“…As discussed in the companion article on the metabolism of anacetrapib in humans (Kumar et al, 2010), the only metabolites detected in biological matrices (plasma and feces) from healthy human volunteers given a single 150-mg oral dose of [ 14 C]anacetrapib were M1, M2, and M3. All of these metabolites were present at much lower levels than those of the parent in human plasma (Ͻ14% of total plasma, radioactivity).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The study showed that anacetrapib does not inhibit or induce CYP3A activity. Furthermore, anacetrapib appears to be a moderately sensitive substrate of CYP3A [37,38].…”
Section: Drug Interaction Studies Of Anacetrapibmentioning
confidence: 98%
“…The pharmacokinetics of anacetrapib have been evaluated in healthy humans, dyslipidemic subjects, and animal models 25,4245. Following a 1-hour delay, anacetrapib is promptly absorbed with peak concentrations arising approximately 4 hours after administration 25,4345.…”
Section: Pharmacokinetics Drug Interactions and Pharmacodynamicsmentioning
confidence: 99%
“…Following a 1-hour delay, anacetrapib is promptly absorbed with peak concentrations arising approximately 4 hours after administration 25,4345. Although anacetrapib is highly plasma protein-bound, the binding is reversible.…”
Section: Pharmacokinetics Drug Interactions and Pharmacodynamicsmentioning
confidence: 99%